Low temperature heteroepitaxial growth of 3C-SiC on silicon substrates by triode plasma chemical vapor deposition using dimethylsilane - Hashim, Abdul Manaf; Yasui, K. (Science Alert, 2008)
The investigation of the dependence of the cubic silicon carbide (3C-SiC) film characteristics on the reaction pressures, growth temperatures and hydrogen dilution rates was carried out by rapid thermal triode plasma CVD using dimethylsilane as a source gas. The stoichiometric 3C-SiC films with good crystallinity and crystal orientation were successfully grown at 1100-1200Â°C. The crystallinity and the crystal orientation of SiC films grown at large dilution rate of above 200 and growth pressure of 0.3-0.7 Torr were better than those grown at small dilution rate and high growth pressure. Under large dilution rate, large amount of hydrogen radicals can be generated. It is speculated that excessive carbon atoms or weak bonds formed in SiC films were effectively extracted by the large amount of hydrogen radicals.